Emerging financial centers : legal and institutional frameworks: Bahamas, Hong Kong, Ivory Coast, Kenya, Kuwait, Panama, Singapore - Effros, Robert C.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1982)
The volume deals with the legal and institutional framework of the financial systems of seven developing economies. the Bahamas, Hong Kong, Ivory Coast, Kenya, Kuwait, Panama and Singapore.
sju 24/01/2019
Loans
Keywords: Banking law; Finance; Money; Securities; Financial institutions